2009
DOI: 10.1080/14639220802368872
|View full text |Cite
|
Sign up to set email alerts
|

Internal representations, external representations and ergonomics: towards a theoretical integration

Abstract: Ergonomics is concerned with how humans interact with systems to perform tasks that achieve goals. This interaction requires thought processes that construct and manipulate mental representations of situations to enable the selection of task-oriented actions having predicted outcomes. The argument for a link between concepts of mental representation and the concerns of ergonomists is a critical theme in the present review, which assesses the current state of knowledge regarding the nature of mental representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 106 publications
(133 reference statements)
0
23
0
2
Order By: Relevance
“…In this study, the associated (self reported) behaviour of participant B closely matched that expected of users holding a 'feedback' theory, so participant B's specific UMM is not of special interest. However, consensus in the literature (e.g Kempton, 1986, Norman, 2002, Peffer et al, 2011, Richardson & Ball, 2009) that UMMs fall into these categories of shared theory is challenged. This suggests that the existence of additional 'shared theories' or unique individual UMMs, that may have a significant impact in terms of energy consuming behaviour, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the associated (self reported) behaviour of participant B closely matched that expected of users holding a 'feedback' theory, so participant B's specific UMM is not of special interest. However, consensus in the literature (e.g Kempton, 1986, Norman, 2002, Peffer et al, 2011, Richardson & Ball, 2009) that UMMs fall into these categories of shared theory is challenged. This suggests that the existence of additional 'shared theories' or unique individual UMMs, that may have a significant impact in terms of energy consuming behaviour, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Kempton, 1986, Norman, 2002, Richardson & Ball, 2009, Peffer et al, 2011. If large proportions of the general UK population also seek out alternate control devices to the thermostat, when making adjustments, it calls into question the present day relevance of Kempton's (1986) insight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In simulating a mental model, a person must operate the mental model while adhering to its constraints. Once formulated, mental models tend to remain static and resistant to change (Richardson and Ball, 2009), until changes to the functionality of the represented system in the real world requires information to be reprocessed in working memory.…”
Section: Cognitive Impairmentmentioning
confidence: 99%